Molecular conservation of Paphiopedilum Rothschildianum And Phalaenopsis Gigantea, two species of endangered orchids in Sabah - Zaleha A. Aziz; Mariam A. Latip; Vijay Kumar Subbiah (Universiti Malaysia Sabah, 2009)
Microsatelites loci in P. rothschildianum and P. gigantea have been isolated and specific molecular markers based on these microsatellite lod developed. These markers were used to characterize population structure of the two endangered orchids. The results have been applied to develop a conservation strategy focused on selective breeding on the basis of genetic distance. In addition, ten molecular markers were developed. These markers have a potential long-term application in population genetic studies, breeding and management programmes and the forensic detection in international trade. Information on the appropriate age of capsules for in vitro germination of seeds has been determined. The germination media for P. rothschildianum and P. gigantea are reported. More than one multiplication media were obtained for both species. These media are simple but effective; coconut water at specific concentration alone was able to induce multiplication of both species, activated charcoal in the multiplication medium was found to have promoting effect on production of P. gigantea protocorm. Seedlings of P. rothschildianum were acclimitised as early as 12 months after germination while that of P. gigantea took around 15 months. Cryoproservation protocols based on vitrification using seeds as explants were developed for both species. Seeds survived liquid nitrogen storage and plantlets of P. rothschildianum were successfully obtained from cyropreserved seeds. Protocorms were successfully recovered from P. gigantea cryopreserved seeds, however the recovery rate was lover as compared to P. rothschildianum. Cryopreservation protocol developed for P. gigantea require testing with high viability seeds. Seeds of P. rothschildianum that had undergone cryopreservation and stored in liquid nitrogen for 6 months had maintained their viability.